Factors associated with mortality in very low birth weight neonates treated with invasive mechanical ventilation at a tertiary hospital in South Africa - Goldstein, Rowan Clive (My University, 2024)
Introduction: Respiratory support with invasive mechanical ventilation (IMV) is a critical intervention available to neonates, especially amongst very low birthweight (VLBW) neonates. Since its introduction in the 1960s it has been associated with an increased survival amongst VLBW neonates. Objectives: To describe the characteristics and outcomes of VLBW neonates who received IMV in the neonatal intensive care unit (NICU) at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods: This was a retrospective, descriptive study of neonates who required IMV admitted to the NICU at CMJAH, between 1 January 2013 and 31 December 2019. The characteristics and outcomes of these neonates were described using univariate analysis. The NICU is combined with the paediatric ICU and comprises of 15 beds. Results: There were 3 484 VLBW neonates admitted during the study period of which 849 required IMV (24.4%). Of the 849, 445 survived (52.4%). 44 infants required high frequency oscillatory ventilation, 16 of whom survived (16/44, 36.4%) making the need for HFOV one of the factors strongly associated with a poor outcome (p<0.001). Other significant associations with poor outcomes were lower birth weight (p<0.001), lower gestational age (p=0.003), the presence of metabolic acidosis (p<0.001), the diagnosis of NEC (p<0.001), pathological cranial sonar findings (p<0.001), and longer length of hospital admission (p<0.001) Conclusion: One quarter of VLBW neonates admitted at CMJAH required IMV during their hospital admission. We demonstrated a survival rate of 52% for ventilated VLBW infants. The only predictive factor for mortality was the presence of metabolic acidosis, likely a surrogate for severity of illness
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Invasive mechanical ventilation; Respiratory support; Low birthweight; SDG-3: Good health and well-being